Effects of labour and product market regulation on worker flows: evidence for the euro area using micro data - Anderton, Robert; Di Lupidio, Benedetta (Nottingham, 2019)
"Evidence using macroeconomic data shows that employment-output elasticities in the euro area increased during the recovery from the crisis, especially in those countries where reforms aimed to facilitate labour market adjustments. In this paper, we investigate whether similar Okun-style empirical relationships show similar changes at the micro level. We econometrically estimate the responsiveness of individual worker flows (i.e. flows of individuals from employment to unemployment and from unemployment to employment) to GDP dynamics in euro area countries during the period 2000-2015; we also investigate whether structural reforms implemented in those countries are associated with a change in the flexibility of job transitions after the crisis. The econometric specifications include, in addition to GDP, micro (individual-level) explanatory variables from the Eurostat Labour Force Survey (EU-LFS) – i.e., socio-demographic variables such as gender, age, and education – in order to capture the key determinants of the individual flows. Overall, the results presented in this paper are consistent with previous results using aggregate data and show a higher responsiveness of individual worker flows to changes in GDP after the crisis, particularly for a group of euro area countries which implemented significant reforms. Moreover, we find that a number of measures which decrease the stringency of regulation (such as reforms which reduce employment protection legislation, product market regulation, and collective bargaining) increase the flexibility of the labour market as they have a positive and statistically significant impact on worker flows."